Administrative openness and diversity in Swiss municipalities: how does local autonomy influence transparency practices?. (December 2020) - Keuffer, Nicolas; Mabillard, Vincent
The increasing demand for transparency has recently fostered greater openness within public administrations. Considered as an essential tool of good governance, transparency helps reinforce the perceived legitimacy of authorities. At the same time, local autonomy has been increasingly embraced in recent decades and recommended by many international institutions. This article combines these two concepts and seeks to highlight the causal relationship that binds them. Given its diversity, Switzerland offers fertile ground for assessing the influence of local autonomy on information-dissemination practices through a comparative perspective. To do so, this article has adopted a mixed approach, based on the creation of a transparency index for two Swiss cantons and on interviews conducted with elected officials from 16 municipalities. The results show, on the one hand, that transparency practices diverge sharply between Swiss municipalities and, on the other hand, that autonomy does have an influence on the degree of transparency at the local level. They encourage further reflection on local government practices and methods to measure what they mean for relations between authorities and citizens. Points for practitioners: In this article, the development of a transparency index provides an insight into the very diverse online information-dissemination practices of Swiss municipalities. It reveals that municipal autonomy has a positive impact on the degree of transparency at the local level. The interviews conducted also show that proximity to citizens makes it possible to circumvent the lack of resources available to smaller municipalities through more direct information channels. These results encourage proactive communication by elected municipal officials.